Reliability of Active Distribution Networks with PV Based Strategic Micro-Grids - Esau, Z.; Jayaweera, Dilan (University of Tasmania, 2013)
The paper presents a new mathematical model for PV (Photo Voltaic) based micro grids and assesses the reliability of an active distribution network with high penetration of PV through strategic micro grids. The key benefit of the model is its flexibility to adapt state transitions of components associated in a PV micro grid. The model works for centralized and decentralized deployment of PV micro grids and captures detailed effects of insolation variations. Case studies are performed incorporating a model of an active distribution network. The results suggest that reliability performance of an active distribution network can be impacted significantly beyond a penetration level of PV with the increased loading of the network.